Uporabnost vodotopnega papirja za zaščito korena zvarka - Pleterski, Matej (Ventil (Ljubljana), 2020)
When welding stain less steel pipes, it is crucial to assure adequate welding conditions inside the pipe where the root is formed. The weld root characteristics need to be mechanically as well as physiochemically acceptable. Weld root protection is achieved by purging the inside of the pipeline with protective gas. The volume of the purging area is of ten limited with various types of barriers of which one is water-soluble paper. This type of purging barriers is usually used when there is no possibility to access the inside of the pipeline after welding. Occasional circumstances, i.e. pressure variations inside the pipeline, present amajor impact on the purging atmosphere establishment. The present paper shows that the water-soluble paper dams are effective only when there is an atmospheric pressure inside the pipe. Even small pressure differences make use of water-soluble paper dams inappropriate and another purging technique shall be utilized.
Keywords: nerjavno jeklo; pipe welding; root purging; stain less steel; varjenje cevi; vodotopni papir; water soluble paper; zaščita korena